Legal Analysis of Movie Reviews on Social Media in Terms of Positive Law - Amrullah, Anwar Hafidz; Asyidqi, Alfi Taufiq; Hasya, Shofiyyah Mardiyyah (Fakultas Hukum, Universitas Islam Bandung, 2024)
Along with the advancement of technology, it has actually facilitated access to movies through various digital platforms. However, to get access to these platforms, people need to subscribe regularly, which not all people can do. This has led to the emergence of the phenomenon of movie reviews on social media which often feature movie trailers which are then monetized, resulting in potential copyright infringement. This research uses normative juridical research methods by collecting legal materials through literature studies. Furthermore, the results of this study show that the practice of movie reviews is actually allowed as long as its use is in accordance with the principle of fair use as stipulated in Article 43 to Article 51 of the HC Law. Based on this principle, the practice of film reviews also cannot be categorized as copyright infringement as long as it meets several conditions, namely non-commercial and permission from the creator. In addition, movie reviews are also not considered to be copyright infringement if the review has included the source in full and does not harm the creator. However, it should be noted that movie reviews on social media that violate copyright provisions can basically lead to legal consequences both in civil and criminal scope.